You are on page 1of 1

xi − µ zα2 / 2 ⋅ σ π2 N!

k = Nn s' 2 =
1
∑ ( xi − x )2
zi = n= k = C Nn =
n!( N − n)! n−1
σ ∆π2

 s' s'   σ σ 
 x − tα /2, n −1 , x + tα /2,n −1   x − zα / 2 , x + zα / 2 
 n n  n n

 p(1 − p ) p(1 − p )   σπ σπ 
 p − tα /2,n −1 , p + tα /2,n −1   p − zα /2 , p + zα /2 
 n n   n n

x − µ0 x − µ0
t calculat = z calculat =
s' / n σ/ n
p −π0 p −π0
t calculat = zcalculat =
p(1 − p) / n σπ / n
x1 − x2 x1 − x 2
zcalculat = t calculat =
σ 12 σ 22 s' 12 s' 22
+
+
n1 n2 n1 n2

x1 − x 2
t calculat = s' 12 ( n1 − 1 ) + s' 22 ( n 2 − 1 )
1 1 s' p =
s' p⋅ + n1 + n 2 − 2
n1 n 2

ESS / k − 1 ESS n − k
Fcalculat = = ⋅
RSS / n − k RSS k − 1

∆ t /0 = yt − y0 ∆ t / t −1 = yt − yt −1

yt yt
it /0 = ( x100) it / t −1 = ( x100)
y0 yt −1

rt /0 = it /0 − 1 ( x100) yt − yt −1
rt / t −1 = ( x100) = it / t −1 − 1 ( x100)
yt −1
∆ n /1 yn − y1
∆= =
n −1 n −1
r = i − 1 (x100)
∑y t
y= t

n
yn
i = n −1
y1